Reaching cardiovascular prevention guideline targets with a polypill-based approach: a meta-analysis of randomised clinical trials. Issue 1 (28th June 2018) - Selak, Vanessa; Webster, Ruth; Stepien, Sandrine; Bullen, Chris; Patel, Anushka; Thom, Simon; Arroll, Bruce; Bots, Michiel L; Brown, Alex; Crengle, Sue; Dorairaj, Prabhakaran; Elley, C Raina; et al.
Abstract : Objective: The aim of this study was to determine the effect of polypill-based care on the achievement of 2016 European Society of Cardiology (ESC) guideline targets for blood pressure (BP), low-density lipoprotein (LDL) cholesterol and antiplatelet therapy. Methods: We conducted an individual participant data meta-analysis of three randomised clinical trials that compared a strategy using a polypill containing aspirin, statin and antihypertensive therapy with usual care in patients with a prior cardiovascular disease (CVD) event or who were at high risk of their first event. Overall, the trials included 3140 patients from Australia, England, India, Ireland, the Netherlands and New Zealand (75% male, mean age 62 years and 76% with a prior CVD event). The primary outcome for this study was the proportion of people achieving ESC guideline targets for BP, LDL and antiplatelet therapy. Results: Those randomised to polypill-based care were more likely than those receiving usual care to achieve recommended targets for BP (62% vs 58%, risk ratio (RR) 1.08, 95% CI 1.02 to 1.15), LDL (39% vs 34%, RR 1.13, 95% CI 1.02 to 1.25) and all three targets for BP, LDL and adherence to antiplatelet therapy (the latter only applicable to those with a prior CVD event) simultaneously (24% vs 19%, RR 1.27, 95% CI 1.10 to 1.47) at 12 months. There was no difference between groups in antiplatelet adherence (96% vs 96%, RR 1.00, 95% CI 0.98 to 1.01). There was heterogeneity by baseline treatment intensity such that treatment effects increased with the fewer the number of treatments being taken at baseline: for patients taking 3, 2 and 0–1 treatment modalities the RRs for reaching all three guideline goals simultaneously were 1.10 (95% CI 0.94 to 1.30, 22% vs 20%), 1.62 (95% CI 1.09 to 2.42, 27% vs 17%) and 3.07 (95% CI 1.77 to 5.33, 35% vs 11%), respectively. Conclusions: Polypill-based therapy significantly improved the achievement of all three ESC targets for BP, LDL and antiplatelet therapy compared with usual care, particularly among those undertreated at baseline.